Effort Being A Journalist In Ahmad Fuadi's The Land Of Five Towers Novel (2011): An Individual Psychological Approach - Fatmawati, Elly; , Drs. Abdillah Nugroho, M. Hum; , Titis Setyabudi, S. S. M. Hum (2013)
The major issue of this study is; how is effort of being a journalist reflected in Ahmad Fuadi's The Land of Five Towers novel (2011)?. The objective of this study is to analyze The Land of Five Towers Novel written by Ahmad Fuadi based on the structural element of the novel and to describe effort being a journalist in Ahmad Fuadi's The Land of Five Towers Novel (2011) based on Individual Psychological Approach. The research is qualitative study. The researcher uses two data sources: primary data source and secondary data source. The primary data source is the novel of Ahmad Fuadi published by Gramedia Pustaka Utama (GPU). The secondary data sources are books or any information related to the practice of effort being a journalist that supported the individual psychological analysis. The data analysis method is descriptive qualitative analysis based on individual psychological approach. The results of the study show; The structural element of the The Land of Five Towers novel shows Alif, Dulmajid, Raja, Atang, Said, and Baso as the major characters and Amak, Fikri Syafnir, Ustad Salman, Kiai Rais and Rajab Sujai as the minor characters. The setting of The Land of Five Towers novel has background in Maninjau, Bukittingggi, West Sumatra, Ponorogo, East Java and Washington DC, United State of America at 2003. The theme of this novel is "The strong want and pray are the major spirit to reach a dream". He must conquer all of the obstacle of life. First the obstacle coming from his family, related with his parents wants to send him to go to religious school after graduation. The second, he must conquer the obstacle of life after he arrives in Madani Pesantren. Alif must knows everything about his new friend, about the situation and the rules within the Pesantren and also all of the assessment from the Pesantren, such as the punishment from the senior, the assessment as a school work, and also the final exam as a final phase in Pesantren. The third, After Alif graduates from Pesantren, he must conquer the obstacle of life related with the foreign people in western, London and Washington.